(untitled) (Международный научный журнал «Инженер», 2026)
This article examines the methods of forming ceramic materials with vermiculite additives and their impact on the structure of these materials. The study compares samples obtained through various shaping technologies, including pressing, casting, and extrusion methods. The research investigates the microstructural changes, porosity levels, and mechanical properties resulting from the addition of vermiculite to the ceramic composition. Additionally, the article analyzes the effect of these materials on crucial properties such as lightness, thermal insulation, and strength. The obtained results serve to expand the potential applications of vermiculite-based ceramic materials in construction, thermal insulation, and other technical fields.